Genetics in the kitchen: an experimental activity in the home extraction of DNA from Kiwi fruit (Actinidia deliciosa) (Research, Society and Development, 2022)
Genetics is one of the most fantastic areas of Biology, and is defined as the science that is concerned with studying the individual in terms of heredity. Endowed with many abstract terms and processes, this area is seen by many students as complex and tedious. In order to overcome these obstacles, with the objective of facilitating the learning of students in the discipline of Biology in High School, we propose in this article an experimental activity of DNA extraction from the kiwi fruit (Actinidia deliciosa), using materials available at home, being these, simple and low cost. With this experimental proposal, we believe that its discussions and problematizations, measured by the teacher, can arouse students' curiosity, in addition to facilitating the learning of topics related to the structure and function of DNA, uniting theory with practice. Another important aspect is that the proposed experimental activity allows stimulating the act of scientific experimentation in students, having great importance in the disciplines of Biology and Science. It is worth noting that this experimental activity can be adapted for virtual or blended teaching, being a very common class model these days due to the pandemic of the new coronavirus (Sars-Cov-2).